Congenital Hydrocephalus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Intrauterine intraventricular hemorrhage occurring about 2 weeks or more prior to birth was the cause of congenital hydrocephalus in 4 newborn infants reported from the Abteilung Neonatologie, Universitats-Kinderklinik, Rumelin-strasse 23; D-7400 Tubingen, FR Germany.